Preserving the sterility of surgical dressings wrapped in paper and other materials - Alder, V. G. (1961)
Materials for wrapping surgical dressings were studied by a method which measured the recontamination rate in packs stored for periods of up to several weeks. Of the materials tested a thick crêpe paper was better than calico and balloon cloth fabrics. Dressings wrapped in paper were not significantly contaminated after storage in dusty places for periods of up to three weeks. For added protection during handling and for convenience in transport and storage, paper packs may be sterilized and kept in paper-lined cartons. The shelf life in good storage conditions would be many weeks at least.